Factors Associated with Safety Riding Behavior Among Workers in Tanjung Priok District, North Jakarta City - Handoko, Handoko; Buntara, Arga; Utari, Dyah; Herbawani, Chahya Kharin (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Introduction: Safety riding behavior is an ideal behavior that any worker must apply to increase the worker’s safety and other road users. There has been an increased prevalence and mortality rate due to traffic accidents in 2022. This study analyzed factors related to driving safety behavior among workers in Tanjung Priok District in 2023.Method: A cross-sectional study was conducted in the Tanjung Priok District between March to June 2023. The questionnaires adopted two instruments from the Indonesian Traffic Police Corps instruments and two previous research instruments distributed through Google Forms. All general workers who reside and work in Tanjung Priok were selected as subjects. The inclusion criteria of this study were workers who both worked or lived in the Tanjung Priok sub-district and ride motorbikes for mobility. The exclusion criteria were individuals who do not work in the Tanjung Priok sub-district and those who only pass through the area without working or residing there. The data were then analyzed using the Chi-square test. The sampling technique applied was proportionate stratified sampling. Result: The finding showed that 97 (86.6%) workers drove safely and 15 (13.4%) workers drove unsafely. The factors associated with safety riding behavior were knowledge (p-value = 0.001), attitude (p-value = 0.007), driving PPE (p-value = 0.010), driving insurance ownership (p-value = 0.046), and family support (p-value = 0.001).Conclusion: Local government is required to cooperate with the police department to increase workers’ knowledge about equipment so safety riding behavior is formed. Latar Belakang: Perilaku keselamatan berkendara merupakan perilaku ideal yang harus dimiliki oleh pekerja untuk meningkatkan keamanan pekerja dan pengguna jalan lain serta meminimalisasi terjadinya kecelakaan lalu lintas. Terjadi peningkatan kasus kecelakaan dan kematian akibat kecelakaan pada tahun 2022 di Jakarta Utara. Penelitian ini bertujuan menganalisis faktor-faktor yang berhubungan dengan perilaku keselamatan berkendara pada pekerja di Kecamatan Tanjung Priok tahun 2023.Metode: Penelitian ini menggunakan desain potong lintang. Penelitian dilaksanakan di Kecamatan Tanjung Priok pada bulan Maret hingga Juni 2023. Instrumen yang digunakan dalam penelitian ini adalah kuesioner yang diadopsi dari instrumen Korps Lalu Lintas Kepolisian Daerah Sumatera Utara dan dua penelitian terdahulu yang disebarkan melalui Google Forms. Sampel penelitian ini adalah seluruh pekerja yang berdomisili dan bekerja di Tanjung Priok dengan kriteria inklusi dalam penelitian ini adalah pekerja yang bekerja dan/atau tinggal di wilayah Kecamatan Tanjung Priok, serta pekerja yang menggunakan sepeda motor untuk mobilitas. Kriteria eksklusi dalam penelitian ini adalah individu yang tidak bekerja di wilayah Kecamatan Tanjung Priok dan hanya melewati wilayah tersebut. Data kemudian dianalisis menggunakan uji chi-square. Teknik pengambilan sampel yang digunakan adalah proporsional stratified sampling. Hasil: Hasil analisis menunjukkan 97 (86,6%) pekerja mengemudi dengan aman dan 15 (13,4%) pekerja mengemudi dengan tidak aman. Faktor yang berhubungan dengan perilaku safety riding adalah pengetahuan (p-value = 0,001), sikap (p-value = 0,007), APD mengemudi (p-value = 0,010), kepemilikan asuransi mengemudi (p-value = 0,046), dan dukungan keluarga. (nilai p = 0,001).Kesimpulan: Kecamatan Tanjung Priok perlu adanya kerja sama dengan kepolisian setempat untuk meningkatkan pengetahuan pekerja mengenai kelengkapan agar terbentuk perilaku keselamatan berkendara. Kata Kunci: Kecelakaan lalu lintas, Keselamatan berkendara, Pekerja